2013
DOI: 10.1039/c2an36359c
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular spectroscopic markers, topography and nanomechanics of human lung cancer and breast cancer cells examined by combined confocal Raman microspectroscopy and atomic force microscopy

Abstract: The nanostructures and hydrophobic properties of cancer cell membranes are important for membrane fusion and cell adhesion. They are directly related to cancer cell biophysical properties, including aggressive growth and migration. Additionally, chemical component analysis of the cancer cell membrane could potentially be applied in clinical diagnosis of cancer by identification of specific biomarker receptors expressed on cancer cell surfaces. In the present work, a combined Raman microspectroscopy (RM) and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 52 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…There is a strong specificity to reflect the changes in biochemical components of living cells in aqueous solutions without any labelling and fixation [7], as such Raman spectroscopy has been employed in clinical diagnostics, toxicology tests, and tissue engineering [8,9]. Raman spectroscopy is a fast, accurate, label-free, and non-destructive analytical tool for the detection of the human cells at the single cell level [10,11]. It can be used to obtain the difference of the intranuclear genetic material between the cancer cells and the normal cells, and the differences of the proteins in the cell membrane and cytoplasm [6,12].…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong specificity to reflect the changes in biochemical components of living cells in aqueous solutions without any labelling and fixation [7], as such Raman spectroscopy has been employed in clinical diagnostics, toxicology tests, and tissue engineering [8,9]. Raman spectroscopy is a fast, accurate, label-free, and non-destructive analytical tool for the detection of the human cells at the single cell level [10,11]. It can be used to obtain the difference of the intranuclear genetic material between the cancer cells and the normal cells, and the differences of the proteins in the cell membrane and cytoplasm [6,12].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Raman spectroscopy is a fast, accurate, label-free, and non-destructive analytical tool for the detection of the human cells at the single cell level [10,11]. It can be used to obtain the difference of the intranuclear genetic material between the cancer cells and the normal cells, and the differences of the proteins in the cell membrane and cytoplasm [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…for classification [40,41]. Figure 7 showed the scatter plots of the SERS spectra for three kinds of miRNAs projected into a two-dimensional subspace using principal component scores PC1 and PC2.…”
Section: Pca Analysismentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) is an ultrasensitive technique that greatly enhances Raman signals of single molecule level [5]. SERS can provide characteristic spectroscopic fingerprints of clinical macromolecules such as a variety of single cells, including cancer cells [6]. Recently, few research groups have already reported the applications of SERS for clinical diagnostics by using labeling NPs agents [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…SERS can provide characteristic spectroscopic fingerprints of clinical macromolecules such as a variety of single cells, including cancer cells [6]. Recently, few research groups have already reported the applications of SERS for clinical diagnostics by using labeling NPs agents [6], [7]. The labeling NPs based SERS application technology, especially for cellular imaging or biomedical diagnostics, still has a strong need for improvement in its sensitivity, selectivity and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%